Short-Course Treatment With Imipramine Entrapped in Squalene Liposomes Results in Sterile Cure of Experimental Visceral Leishmaniasis Induced by Antimony Resistant Leishmania donovani With Increased Efficacy - Mukherjee, Sandip; Pradhan, Supratim; Ghosh, Souradeepa; Sundar, Shyam; Das, Shantanabha; Mukherjee, Budhaditya; Roy, Syamal (Frontiers in Cellular and Infection Microbiology, 2020)
Previously we have shown that long term oral treatment of tricyclic-antidepressant-drug, imipramine, against experimental visceral leishmaniasis, results in clearance of organ parasites, regardless of input infection, either with antimony-sensitive (SbS) or antimony-resistant (SbR) Leishmania donovani (LD) clinical isolates. Although continuous imipramine monotherapy for 28 days (5 mg/kg) results in significant clearance of organ parasites in both SbR and SbSLD infected hamsters, the dose for the sterile parasite clearance from visceral organ is comparatively higher (10 mg/kg) and shows signs of toxicity. Hence, to reduce the toxicity, we encapsulated imipramine in squalene-phosphatidylcholine (SP) liposome (Lip-Imi) and tested its efficacy for a short-course treatment (10 days) in the animal model of visceral leishmaniasis. We observed a significant reduction of hepatic toxicity coupled with sterile parasite clearance in case of this short-course treatment of Lip-Imi, which is absent with free Imi treatment. This also correlates with significant increase in serum availability of imipramine in case of Lip-Imi treatment due to sustained release. Clearance of parasite was coupled with the polarization of antileishmanial immune repertoire from Th2 to Th1 after treatment with Lip-Imi in both SbRLD and SbSLD infected mouse models of LD infection. This study showed that imipramine is effective against both SbSLD and SbRLD at a significantly lower dose with reduced time course of treatment without any toxic side effects, when encapsulated in SP-liposome. Thus, the drug has the potential to be repurposed for the treatment of Kala-azar.